The Head of Madrasa's Leadership Strategy in Improving the Quality of Education in Madrasah Aliyah - Devi Sartika; Deri Wanto; Murni Yanto (EDUKATIF : JURNAL ILMU PENDIDIKAN, 2022)
Good leadership can create a conducive climate to achieve common goals. This study aims to determine the strategies applied by the head of Madrasah aliyah in improving the quality of education at Madrasah Aliyah Ulul Albab Lubuklinggau. The method used in this research is the qualitative method. The results of the study revealed that the head of Madrasah aliyah Ulul Albab carried out strategies to improve the quality of education. The strategy used in improving the quality of education at the madrasah aliyah Ulul Albab is to find staff who are at the appropriate stage of graduation, namely a minimum S1 diploma, applying the 8 pillars contained in the National Education Standards (SNP), dividing the main tasks and functions equally among teachers, and Madrasah leaders. must also be a good example for teachers and students in Madrasahs. The conclusion of this research is that the strategy used by the head of Madrasah aliyah Ulul Albab is to find staff who are at the appropriate graduation stage, namely a minimum S1 diploma, and apply the 8 pillars contained in the National Education Standards (SNP).